2012
DOI: 10.1057/jphp.2012.11
|View full text |Cite
|
Sign up to set email alerts
|

Roles of pharmacists in expanding access to safe and effective medical abortion in developing countries: A review of the literature

Abstract: Unsafe abortion continues to be a major contributor to maternal mortality and morbidity around the world. This article examines the role of pharmacists in expanding women's access to safe medical abortion in Latin America, Africa, and Asia. Available research shows that although pharmacists and pharmacy workers often sell abortion medications to women, accurate information about how to use the medications safely and effectively is rarely offered. No publication covered effective interventions by pharmacists to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 30 publications
(32 reference statements)
3
81
0
1
Order By: Relevance
“…2015b), and the other was a grey literature research report (Zamberlin 2007). The earliest study was published in 1991 (conducted in 1985), but most were published since 2010; 13 of those had not been included in an earlier literature review on this topic (Sneeringer, Billings, Ganatra, and Baird 2012). The studies were conducted in various locations in Latin America (Billings et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2015b), and the other was a grey literature research report (Zamberlin 2007). The earliest study was published in 1991 (conducted in 1985), but most were published since 2010; 13 of those had not been included in an earlier literature review on this topic (Sneeringer, Billings, Ganatra, and Baird 2012). The studies were conducted in various locations in Latin America (Billings et al.…”
Section: Resultsmentioning
confidence: 99%
“…A review of pharmacy provision of MA, published in 2012 (Sneeringer, Billings, Ganatra, and Baird 2012), found that pharmacy workers rarely offer adequate information to women buying MA. Since 2012, however, research on pharmacy and drug shop provision of MA has expanded rapidly.…”
mentioning
confidence: 99%
“…6 Pharmacy workers and drug sellers often bridge the gap between policy and practice in their role as community-based confidants and informants, and play an integral part in information dissemination about abortion. 7,8 By providing advice about health issues, access to medications, and direct service provision, pharmacies serve as a first source of health care to individuals. 7 Pharmacies offer convenience, geographic accessibility, relative anonymity, short waiting times, and relatively inexpensive services compared to that of other health care providers in the formal health system.…”
mentioning
confidence: 99%
“…7,8 By providing advice about health issues, access to medications, and direct service provision, pharmacies serve as a first source of health care to individuals. 7 Pharmacies offer convenience, geographic accessibility, relative anonymity, short waiting times, and relatively inexpensive services compared to that of other health care providers in the formal health system. These advantages may be especially important to people seeking medications for stigmatizing conditions, such as sexually transmitted infections, and for contraception, emergency contraception, and abortion.…”
mentioning
confidence: 99%
See 1 more Smart Citation